2020
DOI: 10.1192/bji.2020.45
|View full text |Cite
|
Sign up to set email alerts
|

Primary care mental health services in Qatar

Abstract: With rapid growth and development in recent decades, the State of Qatar has been redefining strategies and policies towards building a world-class healthcare system. Mental health has emerged as a priority area for development. As a result, mental health services in the region are being redefined and expanded, and this was realised with the launching of the ambitious National Mental Health Strategy in 2013. Traditionally, mental healthcare in Qatar had been considered to be the remit of psychiatrists within se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…There have been no changes in the legal status to reporting suicide since the previous study. However, the population composition and the mental health services in Qatar have undergone significant changes since that time [ 32 – 34 ]. The regular mental health services are provided by the state heavily subsidized and free of charge in emergency to all residents irrespective of the nationality status.…”
Section: Discussionmentioning
confidence: 99%
“…There have been no changes in the legal status to reporting suicide since the previous study. However, the population composition and the mental health services in Qatar have undergone significant changes since that time [ 32 – 34 ]. The regular mental health services are provided by the state heavily subsidized and free of charge in emergency to all residents irrespective of the nationality status.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed that there were many referrals that had insufficient information from the referring doctor. 4,6 There was little justification for urgent referrals. There were referrals that did not conform to the clinical guidelines and were well within the scope of the primary care physician.…”
Section: The Problemmentioning
confidence: 99%
“…This initiative is the first of its kind within the mental health services in this region. 6 These meetings were led by psychiatrists and supported by mental health champions linked to each practice. During these meetings, we used structured feedback questionnaires that we created to collect data about physician demographics, qualifications, years of experience, the training the physicians have received for management of mental disorders and their previous experience of managing mental disorders.…”
Section: The Interventionmentioning
confidence: 99%
“…In recent years, several authors have contributed to a burgeoning body of publications on mental health in Qatar. [1][2][3][4][5] This article builds on this expanding literature by assessing Qatar's progress towards community care as a method for dealing with mental health concerns in the country. This assessment is particularly important at this stage.…”
mentioning
confidence: 99%